Microbial Synthesis Of Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) Copolymer By Cupriavidus Sp. Usmaa2-4 Through A Two Step Cultivation Process - Rahayu Ahmad; Hui-Ling Chai; A. R. M. Yahya; M. I. A. Majid; A. A. Amirul (Academic Journals (Kenya), 2024)
A Gram negative bacterium, Cupriavidus sp. USMAA2-4 was isolated from a soil sample in Northern Peninsular of Malaysia and was able to synthesize polyhydroxyalkanoate containing 4-hydroxybutyrate unit when grown on gggg-butyrolactone as the sole carbon source. The polyester was purified from freeze-dried cells and analyzed by nuclear magnetic resonance (NMR) spectroscopy. 1H and 13C NMR results confirmed the presence of 3HB and 4HB monomers. The isolated strain has the ability to synthesize poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] in a two step cultivation process on a medium containing gggg-butyrolactone as the carbon source. A high fraction of 4HB monomer unit was obtained by manipulating the cell concentration, types of carbon sources and carbon source concentration in the cultivated medium. On the basis of the PHA composition, we suggest that carbon sources such as 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol and 1,12-dodecanediol resulted in a skewed PHA composition. On the other hand, the molar fraction of 4HB in P(3HB-co-4HB) was increased significantly from 25 – 51 mol % by the higher concentration of gggg-butyrolactone as the sole carbon source in the medium. The molecular weight and thermal properties of P(3HB-co-4HB) were revealed by gel permeation chromatography (GPC) and differential scanning calorimeter (DSC), respectively. We found that this bacterium is able to produce wide range copolymer with the number-average molecular weights (Mn) of copolymers ranging from 17 x 103 to 412 x 103 Dalton. Increase in the concentration of gggg-butyrolactone lowered the molecular weight of these copolymers. Higher concentration of gggg-butyrolactone also resulted in more branched polymer and consequently gave lower values for both the glass transition temperature (Tg) as well as melting temperature, Tm.